Evaluation of Protective Biopolymers for Cosmeceutical Applications - Tiwari, Prerna (My University, 2015)
Cosmeceuticals have drug like benefits because of there active ingredients such as vitamins, enzymes, phytochemicals, essential oils, antioxidants and enzymes. Beneficial effect of Cosmeceuticals on human health have attracted increased attention. Antioxidant activity is a very important factor present in cosmeceuticals but mainly artificial antioxidant molecules are used in cosmeceuticals these days. Cosmeceuticals could be more beneficial if natural antioxidant molecules were used instead of artificial antioxidant molecules. In the present study natural biopolymers which were isolated from bacteria and used for the antioxidant activity in Cosmeceuticals. There are diverse structural and functional biopolymers synthesized by bacteria of all taxa and secreted in external environment, bacterial generation in large numbers and biopolymers isolation is a cheaper process. Noble biopolymers were isolated and there antioxidant activities were evaluated in vitro by various assays of antioxidant activity such as- determination of total antioxidant activity, scavenging of Scavenging of 1,1 – diphenyl -2- dipcrylhydrazyl radicals, assay of H2O2 scavenging activity, determination of reducing power. In all the assays of antioxidant activities antioxidant capabilities of various concentration of biopolymers were compared with standard compound and observed the increase in antioxidant activity as the concentration of the biopolymer increases. The biopolymers and the combinations of different biopolymers which were showing the best results during the antioxidant assays, mixed with virgin coconut oil. The concentration of biopolymers added to the coconut oil was dependent on the concentration of biopolymer showing best antioxidant activity in the antioxidant assays. Acid value, in different time periods were noted to find out the biopolymer having best antioxidant activity when applied with the coconut oil. During the experiments bultylated hydroxyl toulene were acting as positive control since it have a good antioxidant activity. There were combination of two polymers which was protecting the oil from degradation throughout the experiment even more than the butylated hydroxyl toulene. The aim of present study was the identification of the type of biopolymers which was having the highest antioxidant activity. The aim of the study was fulfilled since the biopolymers having maximum antioxidant activity was isolated. From the observed results it can be concluded that the synthetic antioxidants can be substituted with the natural biopolymers, or natural antioxidants can be used as antioxidant molecules in the next generation cosmeceuticals.
M.Tech. (Biotechnology)
Keywords: cosmeceuticals; biopolymers; DBT